2020
DOI: 10.15294/jda.v12i1.24811
|View full text |Cite
|
Sign up to set email alerts
|

Utilising SATA in Measuring Students’ Understanding of Financial Statements: A Survey among Non-Accounting Students

Abstract: Accounting is perceived as a complicated process due to its technical difficulties. However, accounting knowledge is undeniable essential to complete a business plan. The ‘Simplified Accounting Template for Apprentice’ (SATA) is developed to facilitate students especially non-accounting students who have very little accounting knowledge in preparing proforma financial statements at the financial section in the business plan. SATA act as integral part of technology used in accounting education to improve studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Accounting students' attitude to entrepreneurship course, entrepreneurial skills development was studied by (Reyad et al, 2019). The level of non-accounting major students' knowledge on accounting through the establishment of automated Simplified Accounting Template for Apprentice in teaching was studied and found that it can assist the students to prepare FStts (Shamsudin et al, 2020). Teaching accounting concepts were insipid and tough to understand mainly for non-accounting major students.…”
Section: Practical Knowledge In Preparing Fsttsmentioning
confidence: 99%
“…Accounting students' attitude to entrepreneurship course, entrepreneurial skills development was studied by (Reyad et al, 2019). The level of non-accounting major students' knowledge on accounting through the establishment of automated Simplified Accounting Template for Apprentice in teaching was studied and found that it can assist the students to prepare FStts (Shamsudin et al, 2020). Teaching accounting concepts were insipid and tough to understand mainly for non-accounting major students.…”
Section: Practical Knowledge In Preparing Fsttsmentioning
confidence: 99%
“…Accounting using information communication technology (ICT) helps increasing student's proficiency in preparing financial statements (Das and Singh, 2018). AFP facilitated non-accounting students to increase understanding in preparing projected financial statements, though they do not have proficiency in preparing financial statements (Shamsudin et al, 2020). Farrelly et al (2018) have described a new faculty-student collaborative curriculum-mapping method by establishing an accounting software program for curriculum review consistent with the Certified Public Accountant (CPA) blueprints that can assist both accounting and non-accounting majored students.…”
Section: Proficiency In Preparing Financial Statementsmentioning
confidence: 99%